Service in the Periphery of the Romanov Empire: Exile or Springboard for Customs Officials of the Administrative Authorities of Czarist Russia in the 19th and Early 20th Centuries? - Krzysztof Latawiec (Colloquia Humanistica, 2023)
Peter I, ruler of Russia, is regarded as the father of the modern administrative apparatus created in order to effectively administer the empire. The then introduced system of personnel selection and promotions became an inherent part of the practice applied during the reign of successive Romanovs until the end of the functioning of absolute rule in Russia. On the basis of preserved source materials of government origin, the fact of the service of customs officials on the borders of the empire was analyzed, as was its influence on appointments to positions within the central administrative authorities that managed the customs revenues of the Romanov Empire in the 19th and early 20th centuries. For some officials, the necessity of serving on the borders of the empire was only a stage in their civil service career, which ultimately ended in the offices operating in the capital city of St. Petersburg. However, many failed to find employment in the capital, pursuing their careers on the borders of the vast Romanov Empire.